Gestión, liderazgo y valores en la administración de centros educativos: Gestión, liderazgo y valores en la administración de la Unidad Educativa Teniente Hugo Ortiz Garcés, de la ciudad de Guayaquil, durante el periodo 2013 – 2014 - Montiel Holguin, Sabina Florencia (2013)
The current research was done at “Tnte. Hugo Ortiz Garces” Military School, where it was analyzed if its staff was performing their responsibilities with excellent educational management, leadership capacity and values practicality. The general objective was achieved since it was possible to evidence that administrators, teachers, students and parents must strengthen the practice of leadership and values. That is the reason for this research having the purpose and approach to become a theoretical and tool reference for the Institutional Educational Project, which will allow to optimize the found critical problems, and fortify the integral education that is pioneered by the institutional mission, as well as the empowerment and engagement of its performers. The current thesis was based on the bibliographical research and field observation; the diagnosis of educational management instruments, organizational structure, SWOT analysis and the application of surveys to administrators, teachers, students and parents; including the administrators interview. From the obtained weaknesses, an improvement proposal is created to fortify the management of the institution on leadership, values and assertive communication.